Analysis of the Results of the Application of Dance Technique Movements as a Strategy for Developing Student - Ningsih, Lora; Devi Lestari, Goesthy Ayu Mariana; Saputri, Amelia Hani (Universitas Negeri Semarang, 2024)
This research aims to reveal the strategies used by SMP N 32 Bandarlampung in developing the talents of its students to face the FLS2N creative dance competition. This research is research that looks at and describes how SMP N 32 Bandarlampung as an educational unit develops its students' interests and talents in dancing to face the National Student Arts Festival and Competition (FLS2N) creative dance branch. To support the dance movement skills of students at SMPN 32 Bandarlampung, it is necessary to carry out physical exercise regularly and correctly before dance training takes place, so that the body can be optimally prepared to carry out dance activities. Strategies for developing student talent interests in aspects of practical facilities for talented students, selection systems for students and trainers, management systems, as well as aspects of time allocation given by schools to students for supporting extracurricular activities. This research used a qualitative method that emphasizes observing the research object paying more attention to the substance of the object being observed and targets class VII and VIII students at SMPN 32 Bandarlampung. Data sources include observations, interviews, and documentation related to dance and sports training. The data analysis techniques include data reduction, data presentation, and conclusion. The results obtained in this research were the discovery of constructive strategies developed by schools in developing their students to develop non-academic achievements, especially in facing the FLS2N creative dance competition.